Glecaprevir/pibrentasvir-associated acute liver injury in non-cirrhotic, chronic HCV infection without HBV co-infection. Issue 5 (24th May 2019) - Hammami, Muhammad Baraa; Aboushaar, Reem; Alsabbagh, Eyad
Abstract : The combination of glecaprevir and pibrentasvir was recently approved for chronic hepatitis C virus (HCV) infection with recommended treatment duration of 8–12 weeks depending on previous treatments, viral genotype and cirrhosis status. Although liver injury was reported with other protease inhibitors in the presence of cirrhosis or hepatitis B virus (HBV) co-infection, glecaprevir/pibrentasvir treatment is not known to cause liver injury. We report a patient with chronic HCV infection who despite the absence of cirrhosis and HBV co-infection developed acute liver injury that completely resolved after glecaprevir/pibrentasvir withdrawal. Interestingly, sustained HCV virologic response was achieved after only 3 weeks of glecaprevir/pibrentasvir treatment.